Microbial Inoculants for Improving Crop Quality and Human Health in Africa - Alori, Elizabeth Temitope; Babalola, Olubukola Oluranti (Frontiers in Microbiology, 2018)
Current agricultural practices that depend heavily on chemical inputs (such as fertilizers, pesticides, herbicides etc) pose deleterious effect on nutritional value of farm produce and health of farm workers and consumers. Excessive and indiscriminate use of these chemicals has resulted in food contamination, weed and disease resistance and negative environmental outcomes which together have a significant impact on human health. Application of these chemical inputs promotes the accumulation of toxic compounds in soils. Highly recalcitrant compound can also be absorbed by some plants. Continuous consumption of such crops can lead to systematic disorders in humans. Quite a number of pesticides and herbicides have carcinogenicity potential. Other principal stationary soil pollution sources include oil refineries, petrochemicals plants and large livestock farms (Dairy cows, pigs and poultry). The increasing awareness of health challenges as a result of consumption of poor quality crops has led to a quest for new and improved technologies of improving both the quantity and quality of crop without jeopardizing human health. A reliable alternative to the use of chemical inputs is microbial inoculants that can act as biofertilizers, biocontrol agents and bioremediators of contaminated soils. Microbial inoculants involve a blend of microorganisms that work with the soil and the soil life to improve soil fertility and health and by extension improve human health. Microbial inoculants have the ability to minimize the negative impact of chemical input and consequently increase the quantity and quality of farm produce. Microbial inoculants are environment-friendly and deliver plant nutrient to plants in a sustainable manner. Microbial inoculants can help reduce chemical fertilizers’ application. Microbial immobilization and mobilization processes affect the bioavailability and mobility of soil contaminants thereby influencing their toxicity and can therefore be used to treat contaminated soil and hence improve the health of consumers of crops grown on such soil. This research summarises the impact of agricultural chemical inputs and metal contaminants on human health. Contribution of microbial inoculant in sustainable maintenance of human health will be expatiated. The role of microbial inoculants in biotransformation of toxic soil contaminants into nontoxic forms will be discussed.